EFFECT OF CHROMIUM ADDITION ON HIDRIDATION PHENOMENA IN ZIRCONIUM ALLOYS FOR NUCLEAR REACTOR APPLICATIONS - Najib Albany, Mohd.
The Fukushima nuclear reactor accident caused by high temperature hidridation when the power generator failed resulted in increased research related to optimizing nuclear reactor cladding. Nuclear reactor cladding functions to prevent fuel corrosion by the coolant and the release of fission products into the coolant. In general, nuclear reactor cladding is made from Zirkonium alloy which has good hardness and hidridation resistance. One solution to optimize nuclear reactor cladding is by combining zirkonium with chromium so that it can increase hardness and hidridation resistance at high temperatures. In this research, the Zr-1 Sn-1 Nb alloy was combined with chromium with composition variations of 0%, 1% and 3%. Each spesimen was hidridized with varying heating temperatures of 700?C and 900?C, and varying heating times of 1 hour and 2 hours. Among the tests carried out including the characterization of the macro structure, micro structure, mechanical properties, chemical composition, and calculation of the rate of hidridation. The test results show that the hardness of zirkonium alloys increases with the amount of chromium alloy, this is also indicated by a tendency for grain refinement with the addition of chromium elements. Then the addition of chromium also increases the hidridation resistance of zirkonium alloys.